Essays on renewable energy and development - Rodrigues, Thiago Antonio Pastorelli (2024)
The three essays in this thesis investigate the local impacts associated with the energy transition toward renewable sources, particularly solar and wind power, for electricity production in Brazil. In recent years, federal and state governments have introduced incentives to promote renewable energy adoption to reduce greenhouse gas emissions and stimulate the economy. However, understanding the cost-benefits of these policies and their effects on the local economy remains limited. Thus, this thesis examines how tax incentives boost small-scale solar energy adoption and how introducing large-scale power plants impacts local labor markets and displaces electricity generation from fossil fuels. Governments have implemented financial incentives to stimulate the development of the small-scale solar photovoltaic (PV) market. Without cost-effective batteries, solar PV owners produce electricity during daylight hours and purchase electricity from the distribution grid at night. The Brazilian states introduced a tax exemption on grid electricity consumption for solar PV owners from 2015 to 2018 to incentivize this technology. In the essay presented in Chapter 1, we investigate the impact of this policy on residential solar PV adoption, considering the staggered implementation across states to identify causal effects. Our findings suggest that the policy positively impacted and accounted for 30% of new installations in the country. This effect translates into an average abatement cost of US$34 per metric ton of CO2, making it a cost-effective policy to contribute to emissions reduction. After examining the effect of an incentive policy on the technology demand, the question arises of how the expansion of renewable energy in Brazil impacts the local labor supply. The employment potential in renewable energy investments can vary depending on the project stage, such as the construction, installation, and operation and maintenance phases. The essay in Chapter 2 examines the impact of utility-scale solar and wind energy investments on local employment before and after power plants begin operations. We utilize administrative data on renewable investments and jobs in Brazil to construct a unique municipal-level panel dataset from 2000 to 2021. By leveraging investments in municipalities, our findings reveal that solar investment boosts local jobs by 7% one year before the power plants open. In contrast, wind energy increased local jobs by 9% over the three years before generation. Additionally, wind projects exhibit a broader impact, attracting new firms and bolstering employment before and after the first electricity generation. Conversely, solar projects attract large firms during the pre-opening phase and have a more localized economic impact. Other significant supply-side effects relate to understanding how renewable energy substitution influences other energy markets. Renewable energy sources can reduce global dependence on fossil fuels for electricity production, but they may also lead to labor market shifts in regions reliant on fossil fuel industries. The essay in Chapter 3 estimates these effects during a period of growth in wind and solar generation in Brazil from 2015 to 2019. We find intermittent renewables partially displace coal and natural gas generation by examining the exogenous hourly variation in solar and wind generation. Using aggregated annual and monthly labor market data at the municipal level, our findings indicate that the increased generation from renewables reduces employment and wages, particularly in municipalities with gas-fired power plants. Increased involuntary dismissals and the end of temporary contracts can explain this effect. Our results provide evidence for the policy debate on supporting a fair and just energy transition.